Моніторинг стану вікової діброви дендрологічного парку “Олександрія” НАН України. Повідомлення І. Санітарний стан - Dragan, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to determine of the modern sanitary condition of the natural ageold oak wood of dendrological park Olexandria and to analyse of its dynamics for the period 2008–2017. Material and Methods. The sanitary condition of the natural oak wood was investigated in dendrological park Olexandria within its 16 sections; oak trees in technogenically polluted ecotops and ecotones; single-growing ageold oaks outside the oak wood. The sanitary condition of the trees was determined by the “Sanitary Rules in the Forests of Ukraine” (1995). The estimation of the condition of individual plantations was given through the planting stock index. The obtained data were compared with similar data from the results of the previous survey as in 2012. Results. In the oak wood dominate (49.1 %) weakened trees (III class), trees without signs of defeat – 16.3 %, with minor damage – 32.6 %, dying trees – 0.9 %, dried trees – 0.7 %. There are no healthy plantations in any section, weakened trees grow on most landscape areas, medium weakened – in degraded, technogenically polluted ecotopes, with a high anthropogenic load, they are strongly weakened on some of last. During the last 5 years the sanitary condition of the oak wood in general, has not changed significantly, on many landscapes, including in unfavorable ecotops, it even improved (0.1–0.4 points). The sanitary condition was deteriorated (0.11 points) on the two areas of the 6th section with recultivation works. Conclusions. The vitality spectra of the age-old oak were determined by the ecological characteristics of the ecotope and were characterized by the predominance of weakened and insignificant proportions of healthy oak trees. In most sections of the oak groves, weakly weeded oak plantations grow, medium and strongly weakened grow in places with tense conditions. During the 5-year period there was a certain stabilization of the sanitary condition of the oak wood, with the exception of two plots in technogenically polluted ecotops.